A Comparative Clinical Study In The Management Of Dushta Vrana, By Sharapunkha Lepa And Jalaukavacharana - Sharath , Kumar M; Raju, M D P; Pachchinavar, K H; Yakkundi, R C; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2020)
Ulcer is a discontinuity, often excavation of skin exhibiting loss of epidermis and portion of the dermis and even sub-cutaneous fat. Despite the fact that wound healing is a natural process it is influenced by both and systemic factors, like micro organism, growth factors, vascularity, and debris. The management of Dushta Vrana has been described in various Ayurvedic texts. Many formulations are in use for centuries. One of these formulations, Sharapunka Lepa has been studied to evaluate its efficacy with Jalaukavacharana in management of Dushta Vrana. It is a single blind study; where in 40 patients were selected for the study. Each group divided into two groups of 20 patients. Group A treated with Sharapunka Lepa. Group B treated with Jalaukavacharana along with Sharapunka Lepa. After the study it is revealed that the Jalaukavacharana along with Sharapunka lepa is having good results in Dustavrana.